Integration of "omics" techniques: Dronedarone affects cardiac remodeling in the infarction border zone. Issue 11 (July 2018) - Chilukoti, Ravi K; Lendeckel, Josefine; Darm, Katrin; Bukowska, Alicja; Goette, Andreas; Sühling, Marc; Utpatel, Kirsten; Peters, Barbara; Homuth, Georg; Völker, Uwe; Wolke, Carmen; Scharf, Christian; et al.
Dronedarone improves microvascular flow during atrial fibrillation and reduces the infarct size in acute models of myocardial infarction. However, dronedarone might be harmful in patients with recent decompensated heart failure and increases mortality in patients with permanent atrial fibrillation. A pathophysiological explanation for these discrepant data is lacking. This study investigated the effects of dronedarone on gene and protein expression in the infarcted area and border zone in pigs subjected to anterior ischemia/reperfusion myocardial infarction. The ischemia/reperfusion myocardial infarction was induced in 16 pigs. Eight pigs were treated with dronedarone for 28 days after myocardial infarction, the remaining pigs served as control. Microarray-based transcriptome profiling and 2D-DIGE-based proteome analysis were used to assess the effects of dronedarone on left ventricular gene expression in healthy (LV), infarcted (MI), and border zone tissue. Selected targets were validated by RT-qPCR or immunoblot analyses, with special emphasize given to the transcriptome/proteome overlap. Combined "omics" analysis was performed to identify most significant disease and function charts affected by dronedarone and to establish an integrated network. The levels of 879 (BZ) or 7 (MI) transcripts and 51 (LV) or 15 (BZ) proteins were significantly altered by dronedarone, pointing to a substantial efficacy of dronedarone in the border zone. Transcriptome and proteome data indicate that dronedarone influences post-infarction remodeling processes and identify matricellular proteins as major targets of dronedarone in this setting. This finding is fully supported by the disease and function charts as well as by the integrated network established by combined "omics". Dronedarone therapy alters myocardial gene expression after acute myocardial infarction with pronounced effects in the border zone. Dronedarone promotes infarct healing via regulation of periostin and might contribute to the limitation of its expansion as well as cardiac rupture. Thus, there are no experimental hints that dronedarone per se has direct harmful effects after MI in ventricular tissue. Impact statement: Dronedarone reduced the infarct size in models of acute myocardial infarction (MI). Here, we show that dronedarone attenuates many of the substantial changes in gene expression that are provoked by acute myocardial infarction (AMI) in pigs. Dronedarone modifies the expression of gene panels related to post-infarction cardiac healing and remodeling processes and, most remarkably, this occurs predominantly in the infarction border-zone and much less so in the vital or infarcted myocardium. Combined "omics" identified matricellular proteins and ECM as major dronedarone-regulated targets and emphasizes their relevance for Disease Charts and Tox Function Charts associated with tissue remodeling and cellular movement. The results demonstrate dronedarone's capability of regulating cardiac repair and remodeling processes specifically in the infarction border zone and identify underlying mechanisms and pathways that might be employed in future therapeutic strategies to improve long-term cardiac tissue function and stability.